جرائم الشيوعية ضد المسلمين في أوزبكستان: Communism crimes against Muslims in Uzbekistan (Khairulummah, 2023)
The Islamic republics, especially the cities of Uzbekistan in Central Asia, are a dear part of the entity of the Islamic world and their history is full of glories. It has a prominent role in spreading Islam and igniting the lamp of Islamic civilization and culture, with what it has produced from distinguished scholars who are distinguished in various sciences and knowledge, such as Imam Al-Bukhari, Al-Tirmidhi, Ibn Sina, Al-Razi and others. They enriched the Islamic heritage with their knowledge and books and writings, which Islamic libraries abound with.And just as the history of the peoples of Central Asia is full of glories, it is also full of tragedies, due to the injustice, oppression and displacement they faced at the hands of the occupying communists and the seizure of their goods and wealth. Although communism has tried to obliterate the identity and culture of the Muslims of Uzbekistan by isolating them from everything related to religion by various means and methods that attempts failed and failed. In removing faith from the hearts of believers who were experience haigh spirit of patient  until almighty Allah SWT permitted them to be released from darkness into light, with the liberation and independence of their countries.
Keywords: Against, Communist, Crimes, Muslims, Uzbekistan